The sleeping aggregative habits of two blue nest renting wasps of the genus Chalybion (Hymenoptera: Sphecidae). (3rd July 2021) - Pham, Phong Huy
ABSTRACT: The sleeping aggregative habits of the two blue nest renting wasps Chalybion bengalense (Dahlbom, 1845) and C. japonicum (Gribodo, 1882) are studied. The two species frequently aggregated on loosely hung strings or leaves for sleeping. The sleeping aggregation was loose and frequently involved both sexes, but males were more numerous than females, or only males in the case of the C. bengalense roost. The presence of C. japonicum in a mixed sleeping aggregation with C. bengalense is reported for the first time. Discussions on the sleeping aggregative habits of the two species are included.